2018
DOI: 10.1002/adma.201706300
|View full text |Cite
|
Sign up to set email alerts
|

Defect Chemistry of Oxides for Energy Applications

Abstract: Oxides are widely used for energy applications, as solid electrolytes in various solid oxide fuel cell devices or as catalysts (often associated with noble metal particles) for numerous reactions involving oxidation or reduction. Defects are the major factors governing the efficiency of a given oxide for the above applications. In this paper, the common defects in oxide systems and external factors influencing the defect concentration and distribution are presented, with special emphasis on ceria (CeO ) based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 84 publications
0
41
0
Order By: Relevance
“…In catalysis, for example, we examine as‐synthesized precursors, catalysts after activation, during operation, and post‐mortem to infer deactivation mechanisms or degradation pathways . R&D research exploits TEM‐related techniques for several classes of materials relevant to the chemical engineering, including metals, ceramics (oxides, carbides, and nitrides,) polymer, and composites materials . TEM is common for probing carbon nanostructures such as nanotubes, nanofilaments, nanohorns, and graphene…”
Section: Applicationsmentioning
confidence: 99%
“…In catalysis, for example, we examine as‐synthesized precursors, catalysts after activation, during operation, and post‐mortem to infer deactivation mechanisms or degradation pathways . R&D research exploits TEM‐related techniques for several classes of materials relevant to the chemical engineering, including metals, ceramics (oxides, carbides, and nitrides,) polymer, and composites materials . TEM is common for probing carbon nanostructures such as nanotubes, nanofilaments, nanohorns, and graphene…”
Section: Applicationsmentioning
confidence: 99%
“…Notably, the BD‐MoS 2 presents a broken lattice, while the as‐prepared MoS 2 shows a nearly defect‐free crystal (Figure f, Figure S6 in the Supporting Information). As shown in Figure g–h, the continuous distributed vacancies of Mo and S atoms are several or even a dozen, which provide the possibility for Na + diffusion in it . From another perspective, the architecture is similar to the tied MoS 2 nanosheets, decreasing the most surface area and side reactions instead of an individual nanosheet …”
mentioning
confidence: 93%
“…Although spinel materials have been widely studied owing to their excellent catalytic activity for OER and ORR, the aggregation or segregation of cations near the surface and interface of catalysts have been frequently captured during the reaction, which has factored heavily into the electrode dynamics and durability. [4] Ap rofound understanding of the correlation between the surface nanostructure and the electrocatalytic performance is then accentuated, which is vital to achieve the rational design of more efficient electrode materials with enhanced stability.Much can be learned from previously reported literature,a sw ell as efforts to control cation segregation for high electrocatalytic activity and durability.F or cobalt-based spinel, during OER operation, the irreversible transformation of Co 2+ oxide to Co 3+ Ohcontaining CoO x (OH) y is accompanied by the weakening of crystallinity.The change of valence state of two or more redox active cobalt atoms,f rom the valence of + 2t o+ 4a nd then reduced, is considered to be the active site in OER, which are connected by m-OH or m-O bridges. [5] Wang et al reported that Co 2+ in tetrahedral sites can be easily oxidized to form CoO x (OH) y ,w hich then acts as the active phase,w hile the Co 3+ in octahedral sites is rather inactive toward the OER as it might be blocked by OH-groups.…”
Section: Introductionmentioning
confidence: 99%